Transient Ischemic Attack : Tantangan dalam Mendiagnosis - Akuba, Nanda Nurrohim; Susianti; Daulay, Suryani Agustina; Berawi, Khairun Nisa (Medula, 2025)
Stroke is a condition characterized by the rapid development of clinical signs of focal and global neurological deficits, which can worsen and persist for 24 hours or more, potentially leading to death, with no clear cause other than vascular. Transient Ischemic Attack (TIA) is a temporary neurological dysfunction caused by a blockade or reduction in blood perfusion to brain tissue, lasting from a few seconds to minutes, and in some cases, up to 24 hours. Diagnosing TIA is challenging because patients typically present after the TIA has resolved, making it crucial to diagnose TIA clinically before confirming the diagnosis with additional examinations such as CT-Scan or MRI. There are meta-analysis studies that describe the role of certain biomarkers in supporting the diagnosis of TIA. Due to the closely related pathomechanisms between TIA and ischemic stroke, almost all the same biomarkers can be used to diagnose both conditions. There are scoring systems used to identify the risk of stroke in patients with TIA, with the ABCD² score being the most commonly used. Rapid assessment and the implementation of adequate therapy reduce the risk of TIA progressing to ischemic stroke.